Long-term outcomes of radiofrequency ablation for intrathoracic goiter up to 5 years: evaluated by computed tomography/magnetic resonance imaging and ultrasound - Yu-Hsin Wang; Pi-Ling Chiang; An-Ni Lin; Cheng-Kang Wang; Chih-Ying Lee; Chen-Kai Chou; Yen-Hsiang Chang; Shun-Yu Chi; Sheng-Dean Luo; Wei-Che Lin (International Journal of Hyperthermia)
Objectives This study evaluated the long-term efficacy and safety of radiofrequency ablation (RFA) for intrathoracic goiter (ITG) over a follow-up period exceeding six months.Methods From 2017 to 2022, 22 patients (6 males, 16 females) with 24 ITGs treated with RFA at a single medical center were evaluated. All patients underwent ultrasonography (US), computed tomography (CT), or magnetic resonance imaging (MRI) before RFA. Follow-up CT/MRI was performed six months after the initial RFA and then every 6–12 months. The primary outcomes measured were the degree of extension, goiter volume, volume reduction rate (VRR), tracheal deviation, and tracheal lumen. Additionally, we assessed the outcomes of single-session RFA (n = 16) vs. multiple sessions (n = 8) on goiters and explored the correlation between ITG volume measurements obtained using ultrasonography and CT/MRI.Results The median follow-up period was 12 months (interquartile range: 6–36.8 months). At the last follow-up, the nodule volume measured by CT/MRI had significantly decreased (76.2 vs. 24.6 mL; p < 0.05), with a VRR of 64.6%. Patients who underwent multiple RFA sessions showed a significantly higher VRR than the single-session patients (63.8 vs. 80.1%, p < 0.05). The intraclass correlation between goiter volumes measured using US and CT/MRI was moderate.Conclusion This study affirms the long-term efficacy and safety of RFA for ITG, providing an alternative treatment for nonsurgical candidates. Multiple RFA sessions may be beneficial for achieving better volume reduction. Sole reliance on ultrasonography is inadequate; therefore, integrating CT/MRI is essential for accurate pre-RFA and follow-up assessments.